Maximizing sponsorship deals for sports clubs & organizations through strategic marketing frameworks - Ševčík, Michal (2025)
This master's thesis aims to develop a strategic marketing framework for sports organizations to maximize sponsorship deals. It investigates how sponsorship practices are shaped and influence the strategic value of these relationships. The research employed a qualitative methodology, conducting semi-structured in-depth interviews with nineteen experts from sports entities and sponsoring companies. Data was analyzed using thematic coding. Key results highlight the critical importance of strategic alignment, individualized proposals, long-term partnerships, proactive outreach, diverse asset articulation, including digital & emotional value, and robust activation. The study concludes that effective sponsorship requires a holistic, relational approach, and it introduces the "Strategic Sponsorship Excellence Framework" to guide organizations.